斜齿圆柱齿轮裂纹扩展特性及剩余寿命研究 - 吴金亮; 汪中厚; 李刚 (Jixie chuandong)
With the development of the modern detection technology,carrying out the gear life prediction with initial crack is of great significance to power transmission device in special situations and precision predict the gear life.Based on the theory of linear elastic fracture mechanics,the stress intensity factor at the different pinion crack positions of a five-speed gear-type transmission is analyzed by using boundary element analysis software FRANC3 D.The crack propagation path and process is explored,and the failure characteristics of crack propagation in the central tooth root and its crack propagation life are predicted.This gear crack propagation research methods is not only enriches the theoretical strength of the gear but also provides a good reference for the optimization of gear design theory.